2013
DOI: 10.1038/cddis.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

Role of α-crystallin B as a regulatory switch in modulating cardiomyocyte apoptosis by mitochondria or endoplasmic reticulum during cardiac hypertrophy and myocardial infarction

Abstract: Cardiac hypertrophy and myocardial infarction (MI) are two major causes of heart failure with different etiologies. However, the molecular mechanisms associated with these two diseases are not yet fully understood. So, this study was designed to decipher the process of cardiomyocyte apoptosis during cardiac hypertrophy and MI in vivo. Our study revealed that mitochondrial outer membrane channel protein voltage-dependent anion channel-1 (VDAC1) was upregulated exclusively during cardiac hypertrophy, whereas 78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
130
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 40 publications
10
130
0
4
Order By: Relevance
“…S4). αB-crystallin was also co-immunoprecipitated with VDAC, consistent with earlier reports (Mitra et al, 2013). The demonstrated associations of desmin and αB-crystallin with VDAC, Mic60 and ATP synthase could somehow facilitate the formation and/or stabilization of a scaffold-like super complex extending from SRmitochondria contact sites to MICOS and ATP complexes.…”
Section: Generation Of Dessupporting
confidence: 90%
See 1 more Smart Citation
“…S4). αB-crystallin was also co-immunoprecipitated with VDAC, consistent with earlier reports (Mitra et al, 2013). The demonstrated associations of desmin and αB-crystallin with VDAC, Mic60 and ATP synthase could somehow facilitate the formation and/or stabilization of a scaffold-like super complex extending from SRmitochondria contact sites to MICOS and ATP complexes.…”
Section: Generation Of Dessupporting
confidence: 90%
“…αΒ-crystallin associates with all three cytoskeletal networks -microfilaments (Bennardini et al, 1992;Singh et al, 2007), microtubules (Arai and Atomi, 1997;Houck and Clark, 2010) and intermediate filaments (Nicholl and Quinlan, 1994;Iwaki et al, 1989;Wisniewski and Goldman, 1998) (reviewed in Wettstein et al, 2012) -and specifically desmin (Bennardini et al, 1992;Nicholl and Quinlan, 1994;Perng et al, 1999). There is also evidence that a fraction of αΒ-crystallin is located in mitochondria (Fountoulakis et al, 2005;Martindale et al, 2005;Maloyan et al, 2005;Mitra et al, 2013); however, its role there is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Divergent signaling mechanisms lead to distinct patterns of cardiac remodeling. The mitogen-activated protein kinase (MAPK) (27) and Akt (1) signaling pathways and matrix metalloproteinases (MMPs) (14) regulate the extracellular matrix and wall stiffness, as well as cardiomyocyte apoptosis pathways (40), including both the mitochondrial and endoplasmic reticulum stress pathways, leading to cell death and contributing to reduced cardiac contractility (21). Inhibition of these pathways in the heart in the setting of increased biomechanical stress remains incompletely understood.…”
mentioning
confidence: 99%
“…Cardiac myocyte apoptosis is a key factor in cardiac remodeling, and it may lead to cell death and contribute to reduced contractility (16,21,40). Previous work has demonstrated that CTSB is closely related to apoptosis (3,4).…”
mentioning
confidence: 99%
“…Thus, we speculate that upon induction during cisplatin treatment, CryAB may accumulate in the mitochondrial membrane to interact with other apoptosis regulatory proteins. In support of this possibility, Mitra and colleagues (25) recently reported that CryAB may interact with voltage-dependent anion-selective channel protein 1, a mitochondrial outer membrane protein that has been implicated in the control of the intrinsic pathway of apoptosis. …”
Section: Discussionmentioning
confidence: 96%